(untitled) - Bergdahl, Michael (Hoboken, N.J., 2006)
Praise for The 10 Rules Of Sam Walton "The 10 Rules of Sam Walton is one of those books that should be read and regularly reread by... everyone-business-people, students, teachers, parents, and children
Keywords: Retail trade,Industrial management,Wal-Mart (Công ty),Quản ltrị công nghiệp,Thương mại bán lẻ; Management,Quản trị,Quản trị